Optimization of an integrated solar heat-pump system - Hawlader, Mohammad Nurul Alam; Shaochun, Ye (IIUM Press, 2011)
This paper describes a method of economic optimization of an integrated solar heat pump system for space cooling, water heating and drying. The system can serve three functions simultaneously or independently. A simulation model for this system was developed to study the influence different variables. The results were validated by a series of experiments carried out under the meteorological conditions of Singapore. Based on this simulation model, an economic optimization was performed to identify the best collector size tor a given load and its distribution. using two methods, life cycle savings (LCS) and payback period. The load pattern is determined based on a typical small hotel with the air-con room area of 500m2, daily hot water demand of 18m3 and daily drying demand of 90 kg. It was seen that the life cycle saving method lead to the prediction of the optimum collector area of 55 m2. The payback period analyses predicted the optimum collector area of 50 m2. The minimum payback period is about 1.5 years.